SNCA: Major genetic modifier of age at onset of Parkinson's disease. Issue 9 (14th May 2013) - Brockmann, Kathrin; Schulte, Claudia; Hauser, Ann‐Kathrin; Lichtner, Peter; Huber, Heiko; Maetzler, Walter; Berg, Daniela; Gasser, Thomas
ABSTRACT Age at onset serves as a predictor of progression and mortality in sporadic Parkinson's disease (PD). Therefore, the identification of genetic modifiers for age at onset might lead to a better understanding of disease pathogenesis. We performed multivariate linear regression analysis in 1396 sporadic PD patients assessing 21 single‐nucleotide polymorphisms (SNPs) that have been previously suggested to be associated with sporadic PD. Moreover, a cumulative risk score was assigned to each patient and correlated with age at onset. We identified the rs356219 risk allele in the SNCA gene as significantly contributing to earlier age at onset. Neither one of the other 21 SNPs tested in this analysis nor the cumulative number of risk alleles showed a significant impact on PD onset. Because sequence variants in the SNCA gene are not only associated with autosomal dominantly inherited PD and increased susceptibility for sporadic PD but also have been found to modify the phenotype such as age at onset in both sporadic and various monogenic forms of PD, this gene serves as an outstanding target for further research on PD pathogenesis, which in return might provide potential therapeutic options. © 2013 Movement Disorder Society